Southern Limestones under Western Eyes - McGowran, Brian (ANU Press, 2024)
Science, the growth of reliable knowledge, became a major triumph of the European Enlightenment in the seventeenth century, under the guise of 'natural philosophy': investigating what the earth and universe are made of and how things work. It took another century for the parallel subject ‘natural history’ to glimpse how the earth, its geography and its richly diverse life came to be. Later, geology and biology became intertwined as biogeohistory—an ever-changing environmental theatre hosting an ever-changing evolutionary play. This environmental theatre has shifted with the making and breaking of supercontinents, the birth and death of global oceans, and the rise and fall of global hothouses and ice ages. The evolutionary play begins with biostratigraphy, wherein fossils revealed deep time and ancient environments and built the first meaningful geological timescale, and ends with the still young science of palaeoceanography—central to which are microfossils, rich in information about the oceans and climates of the past. In Southern Limestones under Western Eyes, Brian McGowran recounts the history of biogeohistory itself: the ever-changing perceptions of rocks, fossils and landscapes, from the late 1600s to the present. McGowran’s focus is southern Australia, the north shore of the dying Australo-Antarctic Gulf, in an era bracketed by two catastrophes: the extinction of dinosaurs and the emergence of humans.